Pengaruh Capital Adequacy Ratio (CAR), Loan Deposit Ratio (LDR) Dan Non Performing Loan (NPL) Terhadap Return On Asset (ROA) Pada Bank Umum Yang Terdaftar Di BEI Periode 2019-2021 - Cahya Akbar Tanaya (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This research aims to determine the influence of the variables Capital Adequacy Ratio (X1), Loan Deposit Ratio (X2) and Non-Performing Loans (X3) on Return On Assets (Y) in Commercial Banks Listed on the BEI for the 2019 - 2021 Period. is quantitative research used to test the relationship of a variable to other variables. The sample selection used the purposive sampling method, the number of samples in the research obtained was 16 financial reports for a period of 3 years, namely 2019-2021, so that a sample of 48 was found. The analysis techniques used were Panel Data Analysis Test, Classical Assumption Test, Hypothesis Test, Coefficient of Determination. The results of the research obtained the panel data regression equation Y= 0.399 + 0.0005CAR + 1.588LDR + 0.833NPL and the t test results of the CAR and NPL variables had a partially significant effect on ROA with a result of <0.05. The LDR variable does not have a partially significant effect on ROA with a result of sig 0.624 > 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that CAR, LDR and NPL have a simultaneous and significant effect on ROA with a sig value <0.05.